Calculation of electronic states of a disordered binary alloy - Yildiz, AK; Celik, FA (Iop Publishing Ltd, 2005)
We present an extension of the Beeby and Hayes method for the calculation of electronic states of a binary disordered alloy in the form A(x)B(1-x) on a square lattice. The calculation demonstrates the application of the disordered system approach to the substitutionally disordered square lattice. The densities of states of the binary alloy are calculated for different cases in the tight-binding limit.
Keywords: Coherent-Potential-Approximation; Cu-Ni Alloys; Systems; Densities